2011
DOI: 10.1002/gcc.20935
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for breast cancer as an integral part of lynch syndrome

Abstract: Lynch syndrome, an autosomal dominant cancer predisposition caused by mutations in DNA mismatch repair (MMR) genes, mainly mainly mutL homolog 1, OMIM 120436 (MLH1) and mutS homolog 2, OMIM 609309 (MSH2), encompasses a tumor spectrum including primarily gastrointestinal, endometrial, and ovarian cancer. This study aimed at clarifying the heavily debated issue of breast cancer being part of Lynch syndrome. Detailed clinical data on cancer occurrence in Swiss female MLH1/MSH2 mutation carriers were gathered, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 36 publications
2
32
1
Order By: Relevance
“…As expected, the gene gyrB which encodes for a subunit of the DNA gyrase is mutated in half of the mutator strains. This is similar to the malfunction in mismatch repair system that was found to contribute to the evolution of cancer cells in mammalian systems 5559 .…”
Section: Discussionsupporting
confidence: 67%
“…As expected, the gene gyrB which encodes for a subunit of the DNA gyrase is mutated in half of the mutator strains. This is similar to the malfunction in mismatch repair system that was found to contribute to the evolution of cancer cells in mammalian systems 5559 .…”
Section: Discussionsupporting
confidence: 67%
“…[7][8][9] Nomenclature and structure of two MMR proteins (MutS and MutL) are conserved from prokaryotes to eukaryotes, but in contrast to bacterial Mut proteins, eukaryotic Mut proteins are heterodimers of two related but distinct proteins. 10 The current study focused on one form of both the major Mut proteins: MutSα and MutLα, in each case using antibodies against both of their constituent proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have suggested there is no increased risk for breast cancer with LS, there has been no consensus to date on the correlation between breast cancer and LS [11,12,13,19,20]. This study revealed that 22.4% of the LS patients meeting NCCN criteria for HBOC had a personal history of breast cancer and a family history of early-onset breast cancer.…”
Section: Discussionmentioning
confidence: 67%